Epidermal cell cultures from white and green sturgeon (Acipenser transmontanus and medirostris): Expression of TGM1-like transglutaminases and CYP4501A - Noreen Karim; Lo-Wei Lin; Joel P. Van Eenennaam; Nann A. Fangue; Andrea D. Schreier; Marjorie A. Phillips; Robert H. Rice (PLoS ONE, 2022)
Using a system optimized for propagating human keratinocytes, culture of skin samples from white and green sturgeons generated epithelial cells capable of making cross-linked protein envelopes. Two distinct forms of TGM1-like mRNA were molecularly cloned from the cells of white sturgeon and detected in green sturgeon cells, accounting for their cellular envelope forming ability. The protein translated from each displayed a cluster of cysteine residues resembling the membrane anchorage region expressed in epidermal cells of teleosts and tetrapods. One of the two mRNA forms (called A) was present at considerably higher levels than the other (called B) in both species. Continuous lines of white sturgeon epidermal cells were established and characterized. Size measurements indicated that a substantial fraction of the cells became enlarged, appearing similar to squames in human epidermal keratinocyte cultures. The cultures also expressed CYP1A, a cytochrome P450 enzyme inducible by activation of aryl hydrocarbon receptor 2 in fish. The cells gradually improved in growth rate over a dozen passages while retaining envelope forming ability, TGM1 expression and CYP1A inducibility. These cell lines are thus potential models for studying evolution of fish epidermis leading to terrestrial adaptation and for testing sturgeon sensitivity to environmental stresses such as pollution.